Rain Attenuation Analysis On VSAT KU-BAND Frequency Meteorological Station of Mopah Merauke - Anna Setyawati; Irwan Krisnadi; Abdul Multi; Agus Sofwan (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
Abstract BMKG is one of the government agencies that provides Meteorological, Climatological, and Geophysic observation data, sent from each Work Unit or Site Sensor. One of the communication media used is VSAT. The Ku-band channel is one of the frequencies used by the BMKG for communication and data transmission. The Ku-band channel has a weakness for propagation, namely rain attenuation. It is necessary to calculate the effect of rain attenuation on the Ku-band channel, in order to obtain efficient power by each earth station. Model ITU-R P.618-5 is one of the rain attenuation prediction models and is generally used for frequencies up to 30 GHz. One of the BMKG station locations that uses the Ku-Band channel is Mopah Merauke Station. With rainfall data of 80.2 mm/hour in Mopah Merauke, ITU-R P.618-5 produces a rain attenuation of 17.86 dB. While the percentage of error with measurement data is 30.1%. Keywords: BMKG, VSAT, Ku-Band, ITU-R P.618-5, Merauke, propagation, attenuation, rain